Trajetórias de vida de professoras negras da Baixada Cuiabana/MT - Moreira, Nilvaci Leite de Magalhães (2013)
In this search investigates the life trajectories of black teacher's who work in public schools in four municipal districts of the Baixada Cuiabá / MT, to know: Cuiabá, Poconé, Nossa Senhora do Livramento and Várzea Grande. The methodological procedure to meet the life way of the teachers was oral history and technique employed was the story of life. All the interviewed teachers originate from humble families, poor income, most is a provider of their homes, and both basic education as the top were won over many difficulties. The teachers' reports showed that racial prejudice and discrimination are still listed in the lives of black women, and daily their intellectual abilities are put to the test, especially when they occupy an important position in the society. Spite of this, they show their capacity through the acquisition of other knowledge able to solidify their social roles. It was found that teachers finding at all times obstacles to discourage them to fight for their ideal, of which impediments were constantly provoked an attempt to get them to remain on the lower bottom of the social hierarchy, however, they relied on a network of support and solidarity that contributed significantly and to overcome obstacles and conquer new spaces such as family and friends. The most of interviewed are ahead of the development of school projects or involved in work aimed at the racial question. The search concluded that with continued education has contributed significantly to the perception of teachers in search of a new pedagogical posture in the racial question.